Leveraging Business Model Components as Drivers of Business Model Portfolios - Sachsenhofer, Wolfgang (Journal of Business Models, 2017)
Purpose: The paper develops a systematic overview of business model portfolios and links it to the diversification literature. It conceptualizes the firm as consisting of multiple, different business models, with the purpose of advancing the structural, organizational and strategic understanding of business models and corporations.

Design: The research design is an in-depth case study focusing on a large European incumbent firm in the automotive industry, secondary data is supported with primary sources.

Findings: Despite its inherently limited nature as a single case study, the paper shows important findings in the study of corporations: A new way thinking of the business model architecture within the rm.

Practical Implications: For practitioners, the paper offers a new toolkit in conceptualizing their firm and shows strategic options in creating, managing and discarding different business models.

Originality / Value: The concept of interlocked business model components as drivers of value creation within business model portfolios offers a new explanation for strategic portfolio creation.
Journal of Business Models, Vol 4 No 3 (2016): Special Issue: New Ways of Developing and Analyzing Business Model Innovation